A new fragment for the understanding of the puzzling evolutive process of the Phymaturus genus: a new species of the patagonicus group from Patagonia, Argentina (Reptilia: Iguania: Liolaemidae) - Scolaro, José Alejandro; Ibargüengoytía, Nora Ruth (Zootaxa, 2008)
A new species, Phymaturus sp. nov. is described as a new member of the Phymaturus patagonicus group of patagonian geographic distribution. It is distinguished by having flat imbricate superciliaries rather than rectangular and non-overlapping, and slightly spiny caudal scales in verticilles. Additionally, the subocular scale is fragmented and separated from the supralabials by two rows of lorilabials (as in most species of the palluma group). The species may be distinguished from other members of the patagonicus group by having metric and meristic differences, as well as a peculiar color pattern characterized by a notorious polychromatism. It lives at about 1000 m of altitude in rocky outcrops near Comallo, in southwestern Rio Negro Province, Argentina. The new species and the closely related species of the patagonicus group are morphologically compared, and its distribution and natural history are described.